Psychological Peculiarities of Understanding by Students Internet Texts - Сергій Максименко; Олена Немеш; Ксенія Максименко; Олександр Набочук (Психолінгвістика)
The purpose of the article is to show psychological peculiarities of understanding by students Internet texts and to determine the predictors of such understanding.